PENGARUH EFEKTIVITAS PROMOSI ABOVE THE LINE DAN BELOW THE LINE TERHADAP DAYA TARIK PENGUNJUNG TAMAN MINI INDONESIA INDAH - Puspasari, Ni Wayan; Febriansyah, Febriansyah (Economic Faculty, Attahiriyah Islamic University, 2018)
This research was aimed for knowing the influence between promotion effectiveness above the line and below the line to the attractiveness of visitor of Taman Mini Indonesia Indah. This research used a quantitative approach through survey to 150 visitors. Using a convenience sampling Hypothesis test (t test) result that shows that the variable above the line affect significantly to these attractiveness of visitor proved by t value about 5,867 which is more than t table. And the variable of below the line affect significantly with t value about 5,345 which is more than t tabel. The conclusion of this research is promotion of above the line and below the line be influential effectively increase the attractiveness of visitors of Taman Mini Indonesia Indah. This means that the promotional media which can increase the wishes of the people for a visit to Taman Mini Indonesia Indah. Keywords: promotion,above the line, below the line, marketing